2019
DOI: 10.1111/psyg.12484
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of cognitive disturbances in mild cognitive impairment: a systematic review of observational studies

Abstract: Mild cognitive impairment (MCI) is an intermediate state between normal cognition and early dementia and is not considered as a typical outcome of brain aging. It has been estimated that 10% to 20% of individuals above 65 years of age will be diagnosed as having MCI. The increased rate of dementia and the importance of early detection of its forerunners have encouraged researchers to focus on detecting MCI and modifiable risk factors with the hope of developing better ways of managing dementia and its conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 78 publications
5
35
0
Order By: Relevance
“…In addition to being strongly correlated with the overall MMSE score, the MoCA showed a good internal consistency, with a Cronbach α of 0.74, like in previous studies [15-19]. In the current investigation, a significant statistical difference in the performance on the MoCA was found between cognitively healthy individuals, patients with MCI, and patients with mild AD, compatible with other studies [6, 15, 20, 21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition to being strongly correlated with the overall MMSE score, the MoCA showed a good internal consistency, with a Cronbach α of 0.74, like in previous studies [15-19]. In the current investigation, a significant statistical difference in the performance on the MoCA was found between cognitively healthy individuals, patients with MCI, and patients with mild AD, compatible with other studies [6, 15, 20, 21].…”
Section: Discussionsupporting
confidence: 90%
“…Our results indicate, in line with previous studies [6, 22, 23], that the Persian version of the MoCA has a high validity for detecting individuals with AD. This result is consistent with the recognized benefits of the MoCA in detection of the early stages of cognitive impairment [18-20, 24], suggesting that the MoCA is a more adequate tool for detection of MCI in the Iranian population. These findings are in consensus with studies from other countries that have revealed that, compared with the MMSE, the MoCA is more sensitive in detecting MCI in different settings and conditions [18, 22, 24].…”
Section: Discussionsupporting
confidence: 88%
“…Mild cognitive impairment (MCI) refers to a transient cognitive state between normal ageing and dementia. MCI is a risk state for Alzheimer's disease (AD) and a common cause of dementia, but MCI is not necessarily leading to AD or other forms of dementia 1,2 . To delay the onset of AD and other forms of dementia, new approaches for precisely identifying the (pre)clinical stages of MCI and effectively treating it are a global health and health‐care priority.…”
Section: Introductionmentioning
confidence: 99%
“…It states that there must be both a subjective and objective decline in one or more of the six cognitive domains, not substantially interfering with instrumental activities of daily living, and not occurring in the context of delirium or other psychological disorders [6,7]. MCI occurs along a continuum from normal cognition to dementia and while not all individuals with MCI progress to AD, MCI alone can decrease quality of life and increase risk of other negative health outcomes [8]. Incidence has been reported to range from a low of 3% to a high of 22% in individuals over 65 years of age [9].…”
Section: Introductionmentioning
confidence: 99%